Impact of armed conflict on crop production in greater Khartoum, Sudan - Sidahmed, Anwar; Mohamed, Shima (International Food Policy Research Institute, 2025)
Since April 2023, Sudan has been engulfed in a violent conflict between the Sudanese Armed Forces and the Rapid Support Forces, resulting in widespread displacement, destruction of infrastructure, and the collapse of essential services. As with agricultural production in rural communities across Sudan, urban and peri-urban farming systems in Greater Khartoum, the area around the capital city, have also been harmed by the conflict.